Analisis Dinamik pada Model Pengendalian Persediaan Dua Produk Berbeda dengan Kapasitas Produksi Terbatas Serta Inisiatif Tim Sales Bersama - Nursanti Anggriani; Eman Lesmana; Asep Supriatna; Hennie Husniah; Mochamad Yudha (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2015)
In this paper we discuss a mathematical model of inventory control policy based on local stability analysis using a system dynamics approach. It is assumed that the production capacity and the maximum production capacity has an upper limit but with sufficient availability of raw materials so that the production occurs continuously without stock out. The model is intended to meet the market equilibrium by determining the optimal number of agents in a team of salesman, the level of inventory, and the level of production capacity, so that thenet income is maximized. We use the Pontryagin Maximum Principle to find the optimal control of the system. Finally some numerical simulations are performed to give a sensitivity analysis of the inventory control policy to the parameters involved in the system.